Influence of SiO2 Filler Addition on the Types I and II Shear Fracture Toughness of Hemp Fiber-Reinforced Epoxy Mixtures. (6th February 2023) - Natrayan, L.; Surakasi, Raviteja; Heaven Dani, M. S.; Patil, Pravin P.; Manikandan, T.; Mannan, K. Tamil; Chewaka, Muse Degefe
Abstract : Natural fiber composites are now more costly than traditional building materials. Currently, industries are moving from traditional materials to natural fiber composites, and the price of natural fiber should be reduced through greater utilization of industrial production. This work aims to determine how matrix alteration affects the interlaminar characteristics of a hemp fiber-reinforced epoxy composite containing nano silicon oxide particles. Interlaminar modulus of rupture in Types I and II is assessed using dual cantilevered beams and end-notched deformation testing samples. Mechanical mixing and sonication are used to blend nanoscale SiO2 (30 nm) into the resin at concentrations of 0, 0.2, 0.4, and 0.6 wt%. The composites were made using the compression molding method. The composites were tested according to the American Society for Testing and Materials standards after manufacturing. The findings show that adding nanoparticles enhances interlaminar toughness values. Interlaminar fracture toughness improved by 20.25% and 30.35% for 0.4 wt% SiO2, respectively. The fiber matrix interaction and failure causes are examined using scanning electron microscope images.